Checklists of Fish Species Infected with Ichthyophthirius multifiliis, the Causative Agent of White Spot Disease, in Iraq - Mhaisen, Furhan T. (Iraqi Journal of Aquaculture, 2023)
Reviewing literature concerning the occurrence of the causative agent of the white spot disease; Ichthyophthirius multifiliis as well as unidentified Ichthyophthirius species, infecting the skin, fins and gills of fishes in Iraq until the end of 2022, showed that 40 fish species are so far known as hosts for I. multifiliis and five fish species for Ichthyophthirius spp. The infected fishes were distributed in different localities of rivers of Iraq, their branches, some lakes, depressions, marshes, drainage networks, fish hatcheries and fish farms in addition to some fishes from fish markets and fish aquaria. These fishes included 24 endemic freshwater fishes, seven exotic freshwater fishes, one marine fish and seven aquarium fishes in addition to one unspecified aquarium fish species.